Anped’s production about initiating teachers and collaborative groups in mathematical education (2000-2015) - Ciríaco, Klinger Teodoro; Morelatti, Maria Raquel Miotto (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
The purpose of this article is to analyze the knowledge production about the investigative tendency of the works published in the annual meetings of the National Association of Postgraduation and Research in Education. For this, a state-of-the-art methodology is used to characterize the production of knowledge about Mathematics Education and Teacher Training in the period from 2000 to 2015. The descriptors used were "Formative Processes and Teaching Learning", "Beginner Teacher Difficulties", "Teacher Training and Teaching Mathematics" and "Teaching Collaboration Contexts". This procedure is justified because of the need to know what has been done in terms of academic research on the subject for validation of a doctoral proposal in education. From data analysis, it is concluded that there is a gap in the production of knowledge in the study of collaborative practices that aim to articulate teachers of different levels of teaching in relation to Mathematics, which reinforces the need to implement initiatives of this nature.